Heterogeneous response of adipose tissue to cancer cachexia - Bertevello,P.S. (2001)
Cancer cachexia causes disruption of lipid metabolism. Since it has been well established that the various adipose tissue depots demonstrate different responses to stimuli, we assessed the effect of cachexia on some biochemical and morphological parameters of adipocytes obtained from the mesenteric (MES), retroperitoneal (RPAT), and epididymal (EAT) adipose tissues of rats bearing Walker 256 carcinosarcoma, compared with controls. Relative weight and total fat content of tissues did not differ between tumor-bearing rats and controls, but fatty acid composition was modified by cachexia. Adipocyte dimensions were increased in MES and RPAT from tumor-bearing rats, but not in EAT, in relation to control. Ultrastructural alterations were observed in the adipocytes of tumor-bearing rat RPAT (membrane projections) and EAT (nuclear bodies).